Análise das escolhas tradutórias dos provérbios no par de obras Ensaio sobre a Cegueira, de José Saramago, e Blindness, por Giovanni Pontiero - Fernandes, Joyce Silva (2014)
Known worldwide for his works and characteristics as a writer, José Saramago breaks paradigms, escapes conventionalism and creates, in his narratives, a new way of treating the vernacular and the conventional practice of novel-writing. By using writing strategies that seek similarity with the speech and the appropriation of forms most commonly employed in speech contexts, such as proverbs, Saramago approaches the reader and develops a reflection on the limits of word meaning. These idiosyncrasies become challenges to the translator that proposes to translate his works, mainly because difficult decisions are made when analyzing what to prioritize in the choices during the translation process. It is important to know and to study translated literary works in order to observe the style of the translator and consequent tendencies in his choices, conscious or not, that modify the work at various levels. The present study aims at analyzing the translation procedures Giovanni Pontiero might have applied in the translation of the work Ensaio sobre a cegueira ([1995] 2009), Blindness (1998). As objectives, we propose to observe and analyze the choices made by the translator, who seems to have given fluency to the text with respect to the translation of the proverbs; identifying the translation modalities characterizing of the solutions found by Pontiero; and recurrence of one or more modalities in the translator s style. The analysis was based on interdisciplinary methodological concepts of comparative literature, defined by Carvalhal (1994, 2005 and 2006) and Coutinho (1994), the translation studies for the application of modalities by Vinay and Darbelnet (1958) and Aubert (1998), as well as studies on the proverbial text, developed by Lopes (1992), Lacerda e Lacerda (2004), Tagnin (2005) and Manser (2007), and the critical fortune of Saramago here composed by Bloom (2005), Reis (2008) and Ornelas (2011)